The Role of Chiropractic Care in the Treatment of Dizziness or Balance Disorders - Harrison Ndetan MSc, MPH, DrPH; Cheryl Hawk DC, PhD; Vishaldeep Ka Sekhon BAMS; Miguel Chiusano DC, MBA, DACNB (SAGE Publishing, 2016)
The purpose of this study was to explore the role of chiropractic in the treatment of dizziness or balance disorders through an analysis of data from the 2008 National Health Interview Survey. Odds ratios and 95% confidence intervals (CIs) were used to assess the likelihood that respondents with dizziness or balance problems perceived that they were helped by specified practitioners. Eleven percent of respondents reported having had a balance or dizziness problem; more than 35% were aged 65 years and older. The odds ratio for perceiving being helped by a chiropractor was 4.36 (95% CI, 1.17-16.31) for respondents aged 65 years or older; 9.5 (95% CI, 7.92-11.40) for respondents reporting head or neck trauma; and 13.78 (95% CI, 5.59-33.99) for those reporting neurological or muscular conditions as the cause of their balance or dizziness.